Role of Scavenger Receptors in Glia-Mediated Neuroinflammatory Response Associated with Alzheimer’s Disease - Francisca Cornejo; Rommy von Bernhardi (Mediators of Inflammation)
It is widely accepted that cells serving immune functions in the brain, namely, microglia and astrocytes, are important mediators of pathological phenomena observed in Alzheimer’s disease. However, it is unknown how these cells initiate the response that results in cognitive impairment and neuronal degeneration. Here, we review the participation of the immune response mediated by glial cells in Alzheimer’s disease and the role played by scavenger receptors in the development of this pathology, focusing on the relevance of class A scavenger receptor (SR-A) for Aβ clearance and inflammatory activation of glial cell, and as a potential target for Alzheimer’s disease therapy.